Koreografi Tari Zapin Bertasbih Pada Sanggar Tasik Malay Art Di Pekanbaru - Yose Fernando; Herlinda Mansyur (FBS Universitas Negeri Padang, 2022)
This research aims to analyze Zapin Bertasbih Dance Choreography in Sanggar Tasik Malay Art Pekanbaru. This type of research is qualitative research with descriptive methods of analysis. The research instrument is the researchers own and is assisted by supporting instruments such as stationery and cameras. Primary data types and secondary data. Data collection techniques are carried out by employing library studies, observations, interviews and documentation. The steps to analyze the data are to describe, interpret and draw conclusions. The results showed that Zapin Bertasbih dance choreography performed by choreographer Tri Sisca Noviani is a new dance creation worked with a choreographic approach. Zapin Bertasbih Dance Choreography can be seen in Form and Content. In the form motion, there are 15 kinds of motion, floor patterns in the form of vertical, horizontal, diagonal and zigzag, the composition of groups in the form of simultaneous and split, dancers (6 people), wearing Malay costumes, dance accompaniment by wearing gambus, accordion, flute, darbuka, marwas and tambur, property using tasbih. In content, among them the idea that arises from taking things done by Muslims in performing worship practices to the creator by using tasbih as his property. The atmosphere that appears in Zapin Dance is peaceful, joyful and calm. Therefore, Zapin Bertasbih Dance is worked on with choreographic planning by his stylist. Because Zapin Bertasbih Dance begins with an idea that departs from Zapin Melayu itself where Zapin Melayu underlies the creation of Zapin Bertasbih. The source of Garapan from Zapin Bertasbih is some movements from Zapin Melayu, namely the movement of worship, Middle Dizziness, Broken Chicks and the Movement of Meniti batang. Then worked by the stylist and arranged movements that have been created into a new form of dance. In content, among them the idea that arises from taking things done by Muslims in performing worship practices to the creator by using tasbih as his property.